2022
DOI: 10.3389/fpls.2022.847435
|View full text |Cite
|
Sign up to set email alerts
|

Combined GWAS and Transcriptome Analyses Provide New Insights Into the Response Mechanisms of Sunflower Against Drought Stress

Abstract: Sunflower is one of the most important oil crops in the world, and drought stress can severely limit its production and quality. To understand the underlying mechanism of drought tolerance, and identify candidate genes for drought tolerance breeding, we conducted a combined genome-wide association studies (GWAS) and RNA-seq analysis. A total of 226 sunflower inbred lines were collected from different regions of China and other countries. Eight phenotypic traits were evaluated under control and drought stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 122 publications
(120 reference statements)
1
12
0
Order By: Relevance
“…5 and 17 under two water conditions, respectively, located on the same chromosome as this study. Interestingly, Wu et al (2022a) found that the SNP locus S5_195713371 was located on chromosome 5 and closely associated with the relative water content of leaves, and this was coincidentally located in the qRLWC-5-1 region in our study. However, it was not at the same loci as this study, which may have been caused by the different densities of the mapping.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…5 and 17 under two water conditions, respectively, located on the same chromosome as this study. Interestingly, Wu et al (2022a) found that the SNP locus S5_195713371 was located on chromosome 5 and closely associated with the relative water content of leaves, and this was coincidentally located in the qRLWC-5-1 region in our study. However, it was not at the same loci as this study, which may have been caused by the different densities of the mapping.…”
Section: Discussionsupporting
confidence: 59%
“…Drought stress was initiated when the seedlings grew to the stage of six leaves. The water stress was carried out according to the method of Wu et al (2022a) . The drought stress (DS) soil moisture content was set to 10 ± 2%, and 30 ± 2% in the control group (CK) ( Wu et al, 2022a ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A genome-wide association study (GWAS) is an effective approach to identify genomic regions associated with specific variants of complex traits, which could dissect more alleles compared with linkage analysis. Recently, GWAS has been widely used to detect important candidate genes associated with yield, quality, salt stress, and drought stress ( Reig-Valiente et al., 2018 ; Luo et al., 2021 ; Hao et al., 2022 ; Wu et al., 2022 ). In barley, many functional loci associated with agronomic traits ( Xu et al., 2018 ), salt stress tolerance ( Mwando et al., 2020 ), drought stress tolerance ( Tarawneh et al., 2020 ), grain quality ( Jia et al., 2021 ) and disease resistance ( Pan et al., 2022 ) have been identified by GWAS.…”
Section: Introductionmentioning
confidence: 99%